1967
DOI: 10.1530/acta.0.0550537
|View full text |Cite
|
Sign up to set email alerts
|

SERUM CONCENTRATION OF Α2-Macroglobulin, HAPTOGLOBIN AND Α1-Antitrypsin IN DIABETES MELLITUS

Abstract: The serum concentration of α2-macroglobulin and that of haptoglobin, the two main components of the electrophoretic α2fraction, and of α1-antitrypsin were studied in a series of outpatients with diabetes mellitus. In all age groups a significant increase of α2-macroglobulin was noted. In adults the increase showed a significant positive correlation with the duration of the disease and was accentuated in the presence of nephropathy with proteinuria. No further increase was noted in the occurrence of other vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Because the majority of serum sialic acid is a component of glycoproteins, such as the acute phase proteins (35), it is relevant that several of the serum acute phase proteins are elevated in diabetes (36)(37)(38), particularly in patients with microvascular complications (36).…”
Section: Results-mentioning
confidence: 99%
“…Because the majority of serum sialic acid is a component of glycoproteins, such as the acute phase proteins (35), it is relevant that several of the serum acute phase proteins are elevated in diabetes (36)(37)(38), particularly in patients with microvascular complications (36).…”
Section: Results-mentioning
confidence: 99%
“…In juvenile diabetic patients raised levels of serum haptoglobin have been reported in patients with angiopathy and increased haptoglobin levels have been shown to be associated with diabetic complications, but not with the duration of the diabetic state [15]. Both fibrinogen and fl-lipoprotein levels, also, have been shown to be related to the incidence of diabetic complications [ 16]. As in this study, it has also been suggested that a2-macroglobulin levels were related to the duration of diabetes [15] although others have shown a progressive rise in a2-macroglobulin levels with an increasing incidence of diabetic vascular complications [17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Studies dating from the 1960s found that individuals with what we now recognize as type 2 diabetes mellitus have higher circulating concentrations of active complement and acute phase reactants (1,2), both of which are classic markers of an inflammatory state. Inflammation is a broad term applied to a variety of processes, but most often indicates stress to an underlying system.…”
Section: Inflammatory Pathways Implicated In Metabolic Diseasementioning
confidence: 99%